Analysis of project management maturity - based on the example of service-oriented companies operating in the public sector - Blaskovics, Bálint; Szabó, Lajos; Kádár, Zsombor; Molnár, Máté; Tóth, Nikolett; Tóth, János (Vezetéstudomány / Budapest Management Review, 2023)
Organisations with a higher level of project management maturity have a higher chance of completing their projects successfully; in this context, they could achieve a competitive advantage over their rivals. Researchers realising this have developed numerous models that could evaluate organisational project management maturity in an appropriate manner. However, the number of models focusing on the public sector is considerably lower, especially if the focus of analysis is companies with numerous service or product development projects. Indeed, appropriate technology management is vital for them. The authors conclude that the model of Cooke-Davies and Arzymanow is suitable for analysing these companies if two other factors, the extent of project management support and the training of the project managers, are added to the original ten criteria. Besides these, the authors identify potential actions that could improve the project management maturity of such organisations.